Barriers to implementing lean construction practices in the Kingdom of Saudi Arabia (KSA) construction industry. Issue 2 (3rd April 2018) - Sarhan, Jamil; Xia, Bo; Fawzia, Sabrina; Karim, Azharul; Olanipekun, Ayokunle
Abstract : Purpose: The purpose of this paper is to identify the barriers to implementing lean construction in the Kingdom of Saudi Arabia (KSA) construction industry and to prioritise the principal factors that constitute these barriers. Design/methodology/approach: A literature review was initially used to reveal the global barriers to implementing lean construction. Subsequently, these barriers were incorporated into a structured questionnaire, and a convenience sample of 282 construction professionals in the KSA construction industry was surveyed. The results were analysed using mean item score (MIS), Mann–Whitney U test and principal component analysis (PCA). Findings: The findings revealed 22 barriers to lean construction implementation in the KSA construction industry. Principal factors that constitute these barriers were found to be traditional practices, client related, technological, performance and knowledge and cost-related barriers in descending order of pervasiveness. The study also proposes solutions to overcome these principal barriers. Originality/value: This study provides a global overview of the barriers to implementing lean construction. It contributes to the body of knowledge, as it uncovers for the first time the barriers to implementing lean construction in the KSA construction industry with reference to the socio-cultural, economic and operational context of the KSA. Thus, it is relevant to other countries in the Middle East because of their shared similarities to the KSA. Furthermore, the solutions proposed to overcome these barriers in the KSA construction industry can be applied in other countries where similar barriers are identified.